(untitled) (Research, Society and Development, 2021)
A multivariate data analysis, evaluating the social and environmental parameters of the state of Tocantins, more specifically the capital, Palmas, was used as a way to understand the causes of self-inflicted violence - suicides. The statistical results showed a strong relationship between the variables age, occupation and sex, while the variable education did not have a great influence. The variables occupation and age group, on the other hand, with 20.7% of the variance, are highly correlated. The variables education, race/color, type of death and place of occurrence did not show any distinction between the samples. It is important to highlight that, in order to change the health reality, it is necessary to strengthen the Policies for the Reduction of Morbimortality from Accidents and Violence and for the Promotion of Health in order to promote equity and improve the conditions of the ways of living, enhancing health and reducing vulnerabilities and risks arising from social, economic, political and environmental determinants.